Hygroma Colli - Basyir, Vaulinne; Utama, Try Genta (Fakultas Kedokteran Universitas Andalas, 2021)
Background : Hygroma coli is a malformation of the lymphatic system in the form of a membrane cyst filled with fluid, limited by the epithelium that is located in the anterolateral or occipito-cervical region. The prenatal diagnosis of cystic hygroma coli by ultrasound is based on an apparently bilateral, mostly symmetrical, and sometimes unilateral cystic structure located in the occipitocervical region. Large hygroma coli can cause pressure on the respiratory tract and digestion, so it requires management as soon as possible.The main treatment modality is surgical excision to remove the cystic lesion. The prognosis of a hygroma coli cyst depends on its size and the action taken because it is rare for cases to experience spontaneous regression.Destination : Reported a case of hygroma colliMethods : Case ReportCase Report : Case 24 years old women with preterm G1P0A0L0 26-27 weeks + Hygroma colli + IUFD + Suspected COVID-19. On ultrasound examination, it was found that BPD =4,71; AC = 15,91; FL = 2,89; EFW = 330 gr; FHR = (-); Cyst = 5,06 x 3,26. The presence of head presentation, IUFD, hygroma colli was found. The patient was planned for labor induction and the progress of labor was followed. Patient provided inform consent that baby was death during pregnancy and need to be labored. The baby was born, weight 300 gr, body length 14 cm and A/S 0/0. Postmortem physical examination revealed findings of hygroma colli infants such membrane cyst filled with fluid that located in the occipito-cervical region. Conclusion: Hygroma colli is a malformation of the lymphatic system and the prognosis or complications depends on the size of cyst. Careful prenatal examination is required in diagnosis and termination of pregnancyKeywords: Hygroma Colli, prenatal diagnosis